Investigating factors affecting the entrepreneurship of women heads of households (case study: women heads of households welfare of Dezful County) - Halajan, Azimeh; Omidian, Faranak; Hosseinpour, Mohammad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Entrepreneurship is a very new phenomenon and a process that plays a vital role in national and even global continuity, growth and development. The topic of women’s entrepreneurship is expanding rapidly, and women’s entrepreneurship is a special and attention-grabbing topic all over the world. The aim of the current research is to investigate the factors influencing the entrepreneurship of women heads of households (a case study of women heads of households in welfare of Dezful city). Method: The research method is of a qualitative type and the statistical population includes all women heads of households who have filed for support services in the Welfare Department of Dezful city. The population size of 70 people who were randomly analyzed with 30 women covered by the welfare department of this city through interviews until the theoretical saturation of factors affecting entrepreneurship among female heads of households. Results: The obtained data were analyzed by the method of theoretical coding including open coding, axial coding and selective coding. The findings showed: To provide a solution, it may be better to divide the category of entrepreneurship and employment of women heads of households into two parts of individual and contextual factors, so that the solution to improve the conditions becomes simpler and more practical. Conclusion: The results of the research show that the group counseling program has an effect on the self-esteem of female heads of households (single and abused). Also, awareness training programs (personal and professional) and entrepreneurship are effective on the self-esteem and entrepreneurial tendencies of female heads of the family.